Brazilian natural dietary components (annatto, propolis and mushrooms) protecting against mutation and cancer - Ribeiro, Lúcia Regina [UNESP]; Mantovani, M. S.; Ribeiro, D. A.; Salvadori, Daisy Maria Favero [UNESP] (Hodder Arnold, Hodder Headline Plc, 2006)
Considering the high number of new cancer cases in Brazil (approximately 470 000 cases in 2005) and the remarkable differences in the incidence of this disease around the world, the development of chemopreventive strategies using foods widely consumed would have a huge impact, both medically and economically. This review summarizes some of our studies conducted to verify the anti-mutagenic and anti-carcinogenic potential of some Brazilian natural dietary constituents (annatto, mushrooms, and propolis). Overall data have shown a clear role for these compounds in preventing mutation and specific preneoplastic lesions. Taken together, these agents indicate a favorable side-effect profile and may prove to be a promising alternative for cancer prevention strategies, although more investigation is needed to fully explore this issue.
Keywords: Agaricus brasiliensis; annatto; anti-carcinogenesis; anti-mutagenesis; Lentinus edodes; propolis